Cardiorespiratory Fitness in Primary Education Pupils: the Association with Anthropometric Characteristics - Gašparović, Matea; Petrić, Vilko; Štemberger, Vesna; Rakovac, Marija; Blažević, Iva (Revija za elementarno izobraževanje, 2017)
The goal of this research was to determine cardiorespiratory fitness (CRF) among primary school male and female pupils and its association with their anthropometric characteristics. The sample consisted of 112 boys and 136 girls, primary school pupils, aged 7 to 10. The Eurofit test battery was used to evaluate anthropometric characteristics (body height, body mass, body mass index (BMI)) and CRF (Beep test to estimate maximal oxygen uptake). The results indicate stagnation in the CRF with chronological age, in both sexes. A statistically significant association (p = 0.001) was shown for all CRF variables and  anthropometric variables except for body height, which was not significantly associated with CRF. An increase in body mass and BMI was associated with a significant (p = 0.001) decrease in male and female pupils' CRF.